Frontiers in algorithmics and algorithmic aspects in information and management : Third Joint International Conference, FAW-AAIM 2013, Dalian, China, June 26-28, 2013. Proceedings - Tan, Xuehou; Zhu, Binhai; Fellows, Michael (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 7th International Frontiers of Algorithmics Workshop, FAW 2013, and the 9th International Conference on Algorithmic Aspects in Information and Management, AAIM 2013, jointly held in Dalian, China, in June 2013. The 33 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 60 submissions. The Joint Conference provide a focused forum on current trends of research on algorithms, discrete structures, operation research, combinatorial optimization and their applications, and will bring together international experts at the research frontiers in these areas to exchange ideas and to present significant new results. The mission of the Joint Conference is to stimulate the various fields for which algorithmics can become a crucial enabler, and to strengthen the ties between the Eastern and Western research communities of algorithmics and applications.